Implementation of Circular Economy Principles in Building Construction Waste - Khiyana, A'izzatul; Suharyanto, Agus; Devia, Yatnanta Padma (ASTONJADRO, 2024)
Building projects often generate significant amounts of waste. This happens because the building projects mostly adopts a linear economic model of “take, make, dispose of”, using materials to the construction of buildings and disposing them at the end of life. This linear economic model only focuses on human activities because the disposal of materials ultimately does not become a sustainable practice in the future. For this reason, an alternative is needed in reducing and processing the construction waste by implementing circular economy principles. This study aims to identify type of construction waste in building project, provide recommendations for handling it with circular economy principles, and calculating the cost savings. The method that used in this study are field observation and interview for collecting data. The result showed that steel reinforcement, ready-mix concrete, light brick, ceramic, multiplex, spun pile, and anchor can be handled with circular economy principles are reduce, reuse, recycle, recovery, and repair. The cost savings from handled it in project A, B, and C are Rp. 68.252.490,65, Rp. 84.182.684,96, and Rp. 31.794.238,51, respectively.